The school and the war, memories between fear and silence - Mauricio Enrique Lizarralde (Corporación Universitaria Minuto de Dios, 2012)
The paper shows some results of the research "Educational environments of schools in areas of armed conflict" developed in the department of Putumayo, under the Interinstitutional Doctorate in Education and under the direction of Dr. Barbara Garcia. It reflects on the role of collective memory in shaping the meanings that come to mediate interactions in schools located in areas of armed conflict, to collect this information was developed field work for two years, an ethnomethodological oriented by the look of the symbolic interactionism perspective. Among the results, this characterization of the different educational environments that there are configured, the reconstruction of the perception of the conflict from the stories, and the role of fear in the significance of interactions, territories and the possibility of reproducing and naturalize violence, ensuring the perpetuation of the conflict.